Turnover Intention Challenges: The Effects Of Financial Compensation, Organizational Climate, And Organizational Commitment - Rizky Atika Salsabila Ivabianca Putri; Septiane Fardhiba Dwi Astuti; Elisabeth Fransiska Sibarani; Salahuddin Rijal Arifin; Almas Farah Dinna Dewi (International Journal of Business and Quality Research, 2025)
This research aims to find out and analyze whether financial compensation, organizational climate, and organizational commitment influence the turnover intention of PT Sumber Alfaria Trijaya Jember’s employees. This type of research is quantitative using primary data sources and secondary data. The research sample used in this research was 78 respondents. The data collection methods used in this research were interviews, questionnaires and literature studies. The data analysis method used is multiple linear regression analysis. The results of this research show that: 1) Financial Compensation has an insignificant positive effect on turnover intention in PT. Sumber Alfaria Trijaya Branch Jember. 2) Organizational climate has a negative and significant effect on turnover intention in PT Sumber Alfaria Trijaya Branch Jember. 3) Organizational commitment has a negative and significant effect on PT turnover intention. Source Alfaria Trijaya Branch Jember. PT. Sumber Alfaria Trijaya should hire & onboard well to esure job fit and smooth integration, pay competitively to offer fair salaries, bonuses, and benefits, giving support career growth to provide training, promotions, and internal mobility, promote work-life balance to lower the turnover intention.